The Effect of Reward and Punishment in Increasing Students’ Motivation to Learn English - Radeni Hapesah (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
This research conducted to know the effect of reward and punishment in learning English at MA Nurul Falah Tg. Marulak in the academic year of 2020/2021. Reward is a tool educated students to able delight on their working got reward and punishment is interpreted as act presenting unpleasant or undiserable consequence certain behaviours. The research used quantitative method with quasi experimental design. The number of population of this research was the class eleventh grade MA Nurul Falah Tg. Marulak and the subject of this research was taken from 25 students of Experimental class and 25 students of control class. The instrument of research used questionnaire and test. The result of questionnaire there were 90% students more loved get reward and punishment and their motivation more increase by used reward and punishment. The data were analyzed by using reward and punishment in experimental class score mean of post-test 87.25 and the score mean post-test in control class was 81,75. At the significance level of α = 0.05 % with df = 48. It can be concluded that reward and punishment gave effect for students’ motivation in learning English at the eleventh-grade students MA Nurul Falah Tg. Marulak.